Analysis and Evaluation of Health Centers Distribution Pattern and Suitability In The Center of Al-Zubair District for the Year 2022 - Abdullah Taher Salman, Lect. Dr. Majda (Basra studies journal, 2024)
The aim of this research is to study the analysis and evaluation of health center distribution patterns in Al-Zubair district, using spatial statistical analysis tools of Geographic Information Systems (GIS) outputs. This is achieved through the application of nearest neighbour analysis, service area analysis based on population and number of centers, and illustrating the results on maps of the study area to diagnose sectors served by well or moderately available health centers, and sectors deprived of health centers. This helps in determining their spatial suitability according to the planning standards of local health centers approved by the Ministry of Health to build a spatial model for selecting the best suitable locations for establishing health centers in Al-Zubair district in the future.